Women-NGOS and financial viability: implications for women empowerment processes from a social work perspective - Mafa, Itai; Kang’ethe, Simon M. (National Association of Social Workers, 2021)
This paper examines the challenges associated with women-NGOs’ financial inadequacy as agents of women empowerment processes in Zimbabwe. With the utility of a resource-dependency theory and a qualitative paradigm, the study discovered that some women-NGOs were downsizing and/or closing due to financial paucity; most of them were skeletal in nature, compromising on coverage. The study also problematizes the donor-dependency syndrome of women-NGOs in Zimbabwe leading to a discourse on the sustainability of these NGOs. The discussion through social work lenses recommended immense advocacy for gender-sensitive policies which can facilitate gender mainstreaming efforts being made by the civil society in light of the current political-economic challenges. A plea for good governance, accountability and a paradigm shift towards developmental interventions aligned to a more integrated approach to solving socio-economic ills is also made in line with the tenets of developmental and critical social work.